The Role of Hormonal Regulation and Brain Neurotransmitters in Baby Blues Syndrome: A Systematic Literature Review - Sari, Ika Novita; Susanti (Sriwijaya Journal of Obstetrics and Gynecology, 2024)
These hormonal fluctuations affect various aspects of maternal health and well-being, including brain neurotransmitters such as serotonin, dopamine, and oxytocin. This is an important aspect in understanding the emotional changes and psychological responses that mothers often experience during this period. This study aimed to present the role of hormonal regulation and brain neurotransmitters in baby blues syndrome. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar). This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. The period of pregnancy and childbirth brings significant hormonal changes in the mother's body. A sharp drop in hormone levels, such as estrogen and progesterone after giving birth, can affect the mother's mood and emotions. Decreased levels of serotonin, a neurotransmitter involved in mood regulation, may contribute to the feelings of sadness and anxiety often experienced by mothers with Baby Blues. Dopamine, a neurotransmitter involved in the regulation of motivation and emotional responses, can also fluctuate due to postnatal hormonal changes, affecting the mother's mood and motivation. Increased cortisol levels in response to physical and emotional stress can impact the mother's mood and can affect the activity of neurotransmitters such as serotonin. Prolactin plays a role in bonding between mother and baby, as well as in breast milk production. These hormonal fluctuations can affect the mother's emotions and feelings.